Programming teaching in high schools: An analysis based on the discourse of collective subject - Mota, Fernanda P.; Adamatti, Diana F. (Frontiers in Education 2015 : launching a new vision in engineering education : proceedings : October 21-24, 2015, Camino Real Hotel & Conference Center, El Paso, Texas, 2015)
This paper presents a qualitative study about programming logic teaching in high school, based on the Discourse of Collective Subject. The project where this study is embedded aims to encourage a greater number of students in the areas of engineering and natural sciences, primarily girls. The main goal is to present how the high school students participating in this project understand issues related to computing learning and women inclusion in this area.